Recent Developments in Normative Trade Theory and Welfare Economics (New Frontiers in Regional Science: Asian Perspectives,, 2018)
This volume examines important topical issues in normative trade theory and welfare economics. In particular, it seeks to investigate how far the potential gainfulness of international trade can be extended in an increasingly globalized world. The first section focuses on the gains from trade in the presence of time-consuming consumption and external increasing returns to scale, which are often neglected in traditional trade theory. The next section considers a range of issues that have practical and policy relevance, including trade liberalization, tax reform, tourism, and international migration. The last section examines the impact of income transfers, both from domestic and international perspectives, and of economic policy making. All chapters of the book are contributed by internationally well-known researchers, including Murray Kemp, Henry Wan, Ngo Van Long and some of Murray Kemp's many colleagues and former students around the world. This book, with its up-to-date information and analysis, will be essential to academics and graduate students in the field of international economics. Trade theorists in research institutions and practicing economists in governmental departments will also find this book of great interest. .